Gambaran karakteristik lanjut usia yang mengalami insomnia di Panti Wreda Dharma Bakti Pajang Surakarta - Mading, Mis Firdaus, H.M Abi Muhlisin, SKM, M.Kep, Kartinah., S.Kep (2015)
Insomnia is a sleep disorder that is most commonly found in the elderly. The prevalence of sleep disorders in the elderly is high at around 67% of the population aged over 65 years. Elderly usually experience physical changes were reasonable, the skin is not tight, the muscles that have been lost and organs are not functioning properly. The aim of this research was describe characteristics of the elderly who experience insomnia at Dharma Bakti Nursing Home of Surakarta. This research used descriptive analytical design with the observesional method obtain through purposive sampling technique. The study population was all elderly aged 60-95 years at Dharma Bakti Pajang Nursing Home of Surakarta some 85 elderly persons. Sample the study were 43 elderly persons. The data of the research were analyzed by using the Insomnia Rating Scale and Geriatric Depression Scale (GDS). The result of the research shows that (1) Most of the respondents aged 60-74 years (2) most of the respondents were female (3) the majority of respondents have a good lifestyle(4) the majority of respondents experiencing mild depression and (5) partially respondents diagnosed with the disease.